Interview with Sergei Nazarenko, - Officer (Soviet-Afghan War & Transnistrian War) -, Conducted in Chișinău, Moldova, 28 August 2018 (RU) - Elisabeth Sieca-Kozlowski (Journal of Power Institutions in Post-Soviet Societies, 2019)
Serguei Nazarenko is a Russian officer trained at the Suvarov school and at the Frunze Academy. He was born in Moldova where his father himself served as an officer. After fighting in Afghanistan, he was sent to Germany, among other places, and then to the military region of Odessa. He was there at the time of the fall of the USSR. He made the choice to swear an oath to the Moldovan army at the beginning of the Transnistrian conflict.